Positron Annihilation Lifetime Study on free Volume Changes in TLD by Gamma - irradiation - Baghdad Science Journal (مجلة بغداد للعلوم, 2004)
Positron annihilation lifetime has been utilized for the first time to investigate the free - volume hole properties in thermolumenscent dosimeter ( TLD ) as a function of gamma-dosc . The hole volume, free volume fraction determined form orthopsitronium lifetime are found to be ?lamatically increase to large values , and then to minimum values as a function ofgamma-dose . The free - volume holes size is found to be 0.163nm’ and to have maximum of 0.166nm^ at the gamma-dose of 0.1 and 0.8 Gy, respectively-